2022
DOI: 10.1073/pnas.2120028119
|View full text |Cite|
|
Sign up to set email alerts
|

A gut microbial peptide and molecular mimicry in the pathogenesis of type 1 diabetes

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by the destruction of pancreatic β-cells. One of the earliest aspects of this process is the development of autoantibodies and T cells directed at an epitope in the B-chain of insulin (insB:9–23). Analysis of microbial protein sequences with homology to the insB:9–23 sequence revealed 17 peptides showing >50% identity to insB:9–23. Of these 17 peptides, the hprt4–18 peptide, found in the normal human gut commensal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 114 publications
1
45
1
Order By: Relevance
“…However, the abundances of Parabacteroides and Alistipes were increased in the phorate-exposed groups compared with those in the control group. Parabacteroides can accelerate the development of diabetes in non-obese diabetic mice as well as increase the macrophage, dendritic cell, and destructive CD8+ T cell levels and reduce the Treg cell levels [ 22 ]. Feeding on HFDs increases the abundance of Alistipes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundances of Parabacteroides and Alistipes were increased in the phorate-exposed groups compared with those in the control group. Parabacteroides can accelerate the development of diabetes in non-obese diabetic mice as well as increase the macrophage, dendritic cell, and destructive CD8+ T cell levels and reduce the Treg cell levels [ 22 ]. Feeding on HFDs increases the abundance of Alistipes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. distasonis colonization in NOD mice has been demonstrated to accelerate diabetes. A molecular mimic of the insulin peptide B:9-23, derived from P. distasonis , previously identified in a DIABIMMUNE study, was shown to activate insulin specific T-cells ex vivo with similar potency ( 29 , 147 ). An integrase derived peptide expressed by several Bacteroides species was found to encode a low avidity mimetope of IGRP 206-214 that can recruit IGRP specific CD8+ T-cells to the GALTs and activate them.…”
Section: Molecular Mimicry In T1dmentioning
confidence: 95%
“…Interestingly, T-cell clones against preproinsulin peptides have shown high cross-reactivity to the peptides of Bacteroides and Clostridium species [ 72 ]. In a NOD mouse model, a peptide produced by Parabacteroides distasonis with homology to β-chain of insulin has been identified [ 73 ]. This peptide can be recognized by T-cells, cross-stimulating an immune response to this chain of insulin [ 73 ].…”
Section: Role Of Gut Microbiota In T1d Pathophysiologymentioning
confidence: 99%
“…In a NOD mouse model, a peptide produced by Parabacteroides distasonis with homology to β-chain of insulin has been identified [ 73 ]. This peptide can be recognized by T-cells, cross-stimulating an immune response to this chain of insulin [ 73 ].…”
Section: Role Of Gut Microbiota In T1d Pathophysiologymentioning
confidence: 99%